Primary care implications of parents nutrition beliefs - Pettigrew, Simone (C S I R O Publishing, 2009)
The present study investigated nutrition-related beliefs and behaviours among parents of varyingsocioeconomic profiles to facilitate more effective primary care interventions to improve parents’ child-feeding practices. A questionnaire comprising attitudinal and behavioural items was administered to parents at three Perth primary schools. A response rate of 21% (n = 181) was obtained. Respondents exhibited a good understanding of most of the issues under investigation, indicating that efforts could focus on changing specific behaviours rather than attempting to increase general awareness of the importance of children’s diets to their health and wellbeing. The results suggest that education relating to appetite regulation could be beneficial to all parents, although medium socioeconomic status families appear to be most in need of this information as well as knowledge relating to repeatedlyoffering new foods to children to foster preference. Information about the need for healthy school canteens and the desirability of reducing television viewing during meals may be more productively targeted to low and medium socioeconomic status families.